Identification of weed dominance and diversity in organic and conventional paddy field (Oryza sativa L.) cultivation - Rahmadi, Rizky; Dulbari, Dulbari; Priyadi, Priyadi; Rochman, Fajar; Pratama, Miandri Sabli (Universitas Muhammadiyah Mataram, 2023)
The presence of weeds in paddy rice crops results in a decrease in yields. Appropriate weed control methods are needed as an effort to reduce potential production losses. The first step to find out the right way to control weeds is by identifying the dominance and diversity of existing weeds. This study aims was to determine the dominance and diversity of weeds in organic and conventional paddy fields. This research was conducted in organic and conventional paddy fields of Lampung State Polytechnic, Lampung Province from October to December 2022. Weeds were observed on the 0.5 m2 quadrant method with 10 replications. The data were analyszed to find the Summed Dominance Ratio (SDR) value to determine the dominant weed and the Shannon - Wiener index (H') value to determine weed diversity. The identification results showed there were 11 weed species in organic land and 7 weed species in conventional land. Broadleaf weeds were the most dominant weeds in both land areas, namely Monochoria vaginalis in organic rice fields and Spenochlea zeylanica in conventional rice fields. The results of the weed diversity index analysis showed that in both land areas fall into the category of moderate diversitywith the value of 2.31 in organic rice fields and 1.93 in conventional rice fields.